Uji Kualitas Air Sungai Bengawanjero Di Desa Bojoasri Kecamatan Kalitengah Kabupaten Lamongan - Robiatul adawiyah; Saimul Laili; Ahmad Syauqi (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2018)
The research has the objective to know the water quality of Bengawanjero River in terms of the quality of physics and chemistry, and compare the test result with the standard quality of water in government rule of Indonesian Republic No. 28 year 2001. Research use Survey-Qualitative and Quantitative Descriptive method. Qualitatively measured parameters were odor, color, taste, depth, current velocity, brightness. Descriptive quantitative parameters were temperature, turbidity, TSS, TDS, Conductivity, Current velocity, Salinity, DO, BOD, CO2, Ammonia, and pH. Color parameters obtained few turbid, ground smell odor and slightly salty taste. Physical parameters; brightness, depth, current velocity, turbidity, TSS, TDS, conductivity of every station fulfill criteria or as classified normal in accordance with water quality standard of No.82 year 2001 for class II. Based on the quality of the Bengawanjero River waters at every station of the chemical parameters; salinity, BOD, CO2, ammonia, and pH fulfill the water quality standard criteria. The condition of the Bengawanjero River in terms of physical and chemical parameters is normal quality. In the Wates, however, the dissolved oxygen value is lower i.e 3.86 than the permitted quality standard with BOD and turbidity values higher than others were possible by organic factor. Keywords: Water Quality, Physical and Chemical Parameter, Bengawanjero River ABSTRAK Penelitian mempunyai tujuan untuk mengetahui kualitas air sungai Bengawanjero ditinjau dari kualitas fisika dan kimia, dan membandingkan hasil uji dengan standar baku mutu kualitas air PP No 28 tahun 2001. Metode yang digunakan adalah metode Survei-Deskriptif Kualitatif dan Kuantitatif. Secara Kualitatif diukur parameter: Bau, warna, rasa, kedalaman, kecepatan arus, kecerahan. Deskriptif kuantitatif adalah parameter : Suhu, Kekeruhan, TSS, TDS, Konduktivitas, Kecepatan arus, Salinitas, DO, BOD, CO2, Amonia, dan pH.. Parameter warna didapatkan agak sedikit keruh, berbau tanah dan rasa agak sedikit asin. Parameter fisika; kecerahan, kedalaman, kecepatan arus, kekeruhan, TSS, TDS, konduktifitas tiap stasiun memenuhi kriteria atau tergolong normal sesuai dengan baku mutu air PP No.82 tahun 2001 untuk kelas II. Berdasarkan kualitas perairan sungai Bengawanjero pada tiap-tiap stasiun dari parameter kimia; salinitas, BOD, CO2, amonia, dan pH memenuhi kriteria baku mutu air. Kondisi sungai Bengawanjero ditinjau dari parameter fisika dan kimia masih tergolong kualitas yang normal. Akan tetapi pada dusun Wates nilai DO lebih rendah yaitu 3,86 dari baku mutu yang diizinkan dengan nilai BOD dan kekeruhan lebih tinggi dibanding lainnya dimungkinkan oleh faktor bahan organik. Kata kunci : Kualitas Air, Parameter Fisika dan Kimia, Sungai Bengawanjero